The progress of music from the early ages to the present time - Perry, Alice (My University, 1903)
Introduction: "0 Music! Thou bringest the receeding waves of eternity nearer to the weary heart of man as he stands upon the shore and longs to cross over! Art thou the evening breeze of this life, or the morning air of the future one?" There are very few people in the world who do not have a natural liking for music in some form or other. All are not interested to the same degree but to many the tracing out of this wonderful art, the means of human expression the gift of the divine, would be full of interest. The term music contains two ideas. The general meaning is that of pleasing modulations of sound. The name music when applied to an art, contains the suggestion of an inspiration. Music has to do with tones selected on account of their musical quality and these tones when joined together, set in order, controlled by human imagination, become music in the artistic sense. Musical development depends upon three conditions; first, the vigor of the mental movement, in general, of the people; second, its strength upon the imaginative and sentimental side; and third, upon the suggestion from the environment in the way of musical instruments of adequate tonal powers. The history of music may be divided into two great periods, ancient and modern, the Christian era forming the dividing line.
Citation: Perry, Alice. The progress of music from the early ages to the present time. Senior thesis, Kansas State Agricultural College, 1903.
Morse Department of Special Collections
Keywords: Musical Instruments; Musicians; History of Music; Music in Greek Theatre; Theses